Building RESTful Web Services with Java EE 8: Create Modern RESTful Web Services with the Java EE 8 API - Reimer, Mario-Leander (Packt Publishing, Limited, 2018)
This comprehensive guide shows you how to use the APIs provided by Java EE to create RESTful web services. You will learn how to use the different JAX-RS APIs in depth. You wil delve into the structure of web services and communicate and share data between applications. Throughout this course, you will develop several fully functional web services.